Logan [videorecording (DVD)] - Stewart, Patrick, 1940-; Jackman, Hugh; Keen, Dafne (20th Century Fox Home Entertainment, 2017)
In the near future, a weary Logan cares for an ailing Professor X in a hide out on the Mexican border. But Logan's attempts to hide from the world and his legacy are up-ended when a young mutant arrives, being pursued by dark forces.